2018
DOI: 10.1093/gastro/gox039
|View full text |Cite
|
Sign up to set email alerts
|

Male gender is associated with an increased risk of anastomotic leak in rectal cancer patients after total mesorectal excision

Abstract: BackgroundThe impact of a patient’s gender on the development of anastomotic leak (AL) in rectal cancer patients following total mesorectal excision (TME) remains controversial. The aim of this study was to evaluate the association between patients’ gender and the risk of AL.MethodsAll rectal cancer patients following TME with a primary anastomosis during the study period from 2010 to 2014 were examined. Comparisons of the post-operative AL incidence rate between male and female patients were performed.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…A similar observation was made in another study conducted in 2003 by Makela et al 6 This result is in contrast with studies that have shown the male gender is an independent risk factor for developing a colonic anastomotic leak. 7,8 It may be because of the presence of multiple risk factors and more number of male patients in our study.…”
Section: Discussionmentioning
confidence: 79%
“…A similar observation was made in another study conducted in 2003 by Makela et al 6 This result is in contrast with studies that have shown the male gender is an independent risk factor for developing a colonic anastomotic leak. 7,8 It may be because of the presence of multiple risk factors and more number of male patients in our study.…”
Section: Discussionmentioning
confidence: 79%
“…The distinction in complications rates might be a result of biologic sex-differences. However, other studies show conflicting results [9,43,45].…”
Section: Current Findings In Contrast To Literaturementioning
confidence: 97%
“…Multiple patient-related factors as well as the severity of the surgical procedure itself are associated with adverse postoperative outcomes [7]. Literature shows that pre-existing comorbidities and sex-related differences are associated with outcome in different surgical populations, and that frail patients have a significantly higher morbidity after elective surgical procedures compared to fit patients [8][9][10]. It is likely that the immune system has a role in the pathogenesis of postoperative complications but few inflammatory biomarkers are established to further estimate the risk of postoperative complications across populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies included in the literature survey evaluated smoking as a risk factor for AL and, of these, nine 3,11,13,20,26,31,42,51,55 showed significant differences between smokers and non-smokers.…”
Section: Smoking Habitsmentioning
confidence: 99%
“…According to previous studies, the predictors of AL are male sex, coronary artery disease, type of surgical procedure, elevated serum albumin, low rectal anastomosis and neoadjuvant radiotherapy 3,4 .…”
Section: Introductionmentioning
confidence: 99%